Proof of Concept Design for Identification of Late Blight on Potato Leaves Using a UAV - Sullca Bendezu, Romi Vianne (2025)
Potato is the third most consumed food fruit worldwide by humans and on many occasions at planting time it is affected by numerous fungal species that generate various diseases in potato leaves and tubers, causing great economic losses and obtaining a poor crop production. The objective of this study was to design a proof of concept for the early identification of late blight disease in potato leaves using an unmanned aerial vehicle (UAV), under the terms of technical and economic evaluation of the solution and the concepts of using an embedded system. The late blight identification processes were exposed to the technical and economic evaluation of the solution from three proposed solutions, solution S 1, solution S 2 and solution S 3. The three provided solutions were compared, and the following results were obtained, the technical values Xi obtained the results of 0.86, 0.68 and 0.75 according to the order number of solutions one, two and three and the economic evaluation results obtained the economic values Yi of 0.88, 0.79 and 0.75. The optimal solution for the design of the proof of concept for the identification of late blight on potato leaves is solution S 1, and from it the design of the control flow diagram and the schematic communication diagram were developed.